Model Optimasi Goal Programming Pada Perencanaan Produksi Roti - Purba, Wesly Tua Panuturi; Br Sinaga, Juli Antasari; Sianturi, Rektor (Jurnal Indragiri Penelitian Multidisiplin, 2024)
In the preparation of production planning, the goal to be achieved is not only one. Roti Sultan Meriah is a small and medium enterprise engaged in the production of bread. Roti Sultan Meriah aims to meet market demand and must also consider the costs used during the production process so that the profit obtained is maximized. In this study, the solution to the problem was solved by using the application of the goal programming method where this method can solve more than one goal, unlike in linear programming. The goal programming method used is a model with goal priority. The goal programming method with goal priority allows Roti Sultan Meriah to optimize various aspects of production simultaneously, such as meeting market demand, minimizing costs, and maximizing profits. This approach allows the company to prioritize these goals, so that it can make better decisions in production planning. By using this method, Roti Sultan Meriah can increase its operational efficiency and competitiveness in the competitive bread market. The results of this study obtained an optimal solution, namely the achievement of the sales volume target, production costs that do not exceed the target limit of Rp. 27,511,230, - and the profit target is achieved, namely Rp. 98,764,373, - for a period of one year